DEVELOPMENT AND VALIDATION OF ULTRAVIOLET SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF MEBHYDROLINE NAPADISYLATE IN TABLET PREPARATIONS - Nerdy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective : Mebhydrolin Napadisylate is classified as an antihistamine drug classes used to treat allergies. One of the quality requirements for drug preparation was active compound levels must meet the requirements as stated in the Pharmacopoeia or other standard books. The purpose of this study was to validate an ultraviolet spectrophotometric method of determination of Mebhydrolin Napadisylate in the tablet preparation available in the market. Methods : Solvents used are hydrochloric acid (HCl) 0.1 N in methanol and sodium hydroxide (NaOH) 0.1 N in methanol for determination of Mebhydrolin Napadisylate and has not been reported. The ultraviolet spectrophotometric method used in the determination of Mebhydrolin Napadisylate will be conducted validation which includes: accuracy, precision, linearity, range, limit of detection (LOD) and limit of quantitation (LOQ). Results : Measurements were made at a maximum wavelength (Î»max) of Mebhydrolin Napadisylate 287 nm. Results of ultraviolet spectrophotometric method validation in determination of Mebhydrolin Napadisylate in tablet preparation; accuracy, precision, linearity, range, limit of detection (LOD), and limit of quantitation (LOQ) meet the requirements of validation tests for methods of analysis. The obtained results of the determination of Mebhydrolin Napadisylate levels in tablet preparation with a branded name on the market meet the general requirements of tablet preparation. Conclusion : Ultraviolet spectrophotometric method of Mebhydrolin Napadisylate determination in tablet preparation meets the requirements of validation tests for methods of analysis. The determination of Mebhydrolin Napadisylate levels in tablet preparation meets the general requirements of tablet preparation. Keywords : Development, Validation, Ultraviolet Spectrophotometric, Mebhydroline Napadisylate